Gut microbiome reflect adaptation of earthworms to cave and surface environments - Gong, Xin; Chen, Ting-Wen; Zhang, Lili; Pižl, Václav; Tajovský, Karel; Devetter, Miloslav (Animal microbiome, 2022)
BACKGROUND: Caves are special natural laboratories for most biota and the cave communities are unique. Establishing population in cave is accompanied with modifications in adaptability for most animals. To date, little is known about the survival mechanisms of soil animals in cave environments, albeit they play vital roles in most terrestrial ecosystems. Here, we investigated whether and how gut microbes would contribute to the adaptation of earthworms by comparing the gut microbiome of two earthworm species from the surface and caves. RESULTS: Two dominant earthworm species inhabited caves, i.e., Allolobophora chlorotica and Aporrectodea rosea. Compared with the counterparts on the surface, A. rosea significantly decreased population in the cave, while A. chlorotica didn't change. Microbial taxonomic and phylogenetic diversities between the earthworm gut and soil environment were asynchronic with functional diversity, with functional gene diversity been always higher in earthworm gut than in soil, but species richness and phylogenetic diversity lower. In addition, earthworm gut microbiome were characterized by higher rrn operon numbers and lower network complexity than soil microbiota. CONCLUSIONS: Different fitness of the two earthworm species in cave is likely to coincide with gut microbiota, suggesting interactions between host and gut microbiome are essential for soil animals in adapting to new environments. The functional gene diversity provided by gut microbiome is more important than taxonomic or phylogenetic diversity in regulating host adaptability. A stable and high-efficient gut microbiome, including microbiota and metabolism genes, encoded potential functions required by the animal hosts during the processes of adapting to and establishing in the cave environments. Our study also demonstrates how the applications of microbial functional traits analysis may advance our understanding of animal-microbe interactions that may aid animals to survive in extreme ecosystems.
Keywords: Cave; Rrn; Network stability; Gut microbiome; Functional diversity; Earthworms